Chaos-assisted two-octave-spanning microcombs - Chen, Hao-Jing; Ji, Qing-Xin; Wang, Heming; Yang, Qi-Fan; Cao, Qi-Tao; Gong, Qihuang; Yi, Xu; Xiao, Yun-Feng (Nature communications, 2020)
Since its invention, optical frequency comb has revolutionized a broad range of subjects from metrology to spectroscopy. The recent development of microresonator-based frequency combs (microcombs) provides a unique pathway to create frequency comb systems on a chip. Indeed, microcomb-based spectroscopy, ranging, optical synthesizer, telecommunications and astronomical calibrations have been reported recently. Critical to many of the integrated comb systems is the broad coverage of comb spectra. Here, microcombs of more than two-octave span (450 nm to 2,008 nm) is demonstrated through χ (2) and χ (3) nonlinearities in a deformed silica microcavity. The deformation lifts the circular symmetry and creates chaotic tunneling channels that enable broadband collection of intracavity emission with a single waveguide. Our demonstration introduces a new degree of freedom, cavity deformation, to the microcomb studies, and our microcomb spectral range is useful for applications in optical clock, astronomical calibration and biological imaging. Here, the authors demonstrate the use of chaos to obtain 2-octave comb generation. The deformation lifts the circular symmetry and creates chaotic tunneling channels that enable broadband collection of intracavity emission with a single waveguide, introducing a new degree of freedom to microcomb studies.